Anterior cruciate ligament reconstruction and knee osteoarthritis - Paschos, Nikolaos K (World J Orthop, 2017)
Anterior cruciate ligament (ACL) injury is a traumatic event that can lead to significant functional impairment and inability to participate in high-level sports-related activities. ACL reconstruction is considered the treatment of choice for symptomatic ACL-deficient patients and can assist in full functional recovery. Furthermore, ACL reconstruction restores ligamentous stability to normal, and, therefore, can potentially fully reinstate kinematics of the knee joint. As a consequence, the natural history of ACL injury could be potentially reversed via ACL reconstruction. Evidence from the literature is controversial regarding the effectiveness of ACL reconstruction in preventing the development of knee cartilage degeneration. This editorial aims to present recent high-level evidence in an attempt to answer whether ACL injury inevitably leads to osteoarthritis and whether ACL reconstruction can prevent this development or not.